2004
DOI: 10.1242/jcs.01303
|View full text |Cite
|
Sign up to set email alerts
|

Outer dense fibre protein 2 (ODF2) is a self-interacting centrosomal protein with affinity for microtubules

Abstract: Outer dense fibre protein 2 (ODF2) is a major protein of sperm tail outer dense fibres which are prominent sperm tail-specific cytoskeletal structures. Moreover, ODF2 was also identified as a widespread component of the centrosomal scaffold and was found to associate preferentially with the appendages of the mother centriole [Nakagawa, Y., Yamane, Y., Okanoue, T., Tsukita, S. and Tsukita, S. (2001) Mol. Biol. Cell 12, 1687-1697]. Secondary structure predictions indicated ODF2 as an overall coiled-coil protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0
13

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(70 citation statements)
references
References 48 publications
(78 reference statements)
3
54
0
13
Order By: Relevance
“…3). These proteins are associated with the development of sperm tails, where they provide elasticity and protection from shear [41]. Interestingly, up-regulation of opsins was also observed in males with respect to androchrome and infuscans female morphs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3). These proteins are associated with the development of sperm tails, where they provide elasticity and protection from shear [41]. Interestingly, up-regulation of opsins was also observed in males with respect to androchrome and infuscans female morphs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…ODF2, Hexokinase, and Aldolase C Outer dense fiber protein 2 (ODF2) is a major component of the cytoskeletal structure of the sperm tail and is associated, albeit indirectly, with microtubules [67]. Hexokinase binds ATP in an actin fold-like structural motif to phosphorylate glucose, and it has been localized in the acrosome, midpiece, and tail of human spermatozoa [68,69].…”
Section: Rhoa-interacting Proteins In Bovine Spermatozoamentioning
confidence: 99%
“…ODF2 is a putative coiled coil protein containing two leucine zippers that mediate interaction with ODF1, another major component of the outer dense fibers (Donkor et al, 2004;Shao et al, 1997). A critical function of Odf2 is implied by strong sequence conservation (Petersen et al, 1999): for example, the amino acid sequences of human and mouse ODF2 share greater than 97% homology.…”
Section: Introductionmentioning
confidence: 99%
“…However, in a recent publication, monoclonal antibodies directed against purified chicken centrosomes have identified ODF2 protein as a widespread centrosomal component (Nakagawa et al, 2001). Further studies have also suggested that ODF2 protein at the centrosome is able to associate both with itself and with microtubules (Donkor et al, 2004). Furthermore, an Odf2 gene targeted knockout mouse F9 cell line has recently been described, in which a critical role for ODF2 at the centrosome for the generation of primary cilia was revealed (Ishikawa et al, 2005).…”
Section: Introductionmentioning
confidence: 99%